BS EN IEC 61300-3-14. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 3-14. Examinations and measurements. Error and repeatability of the attenuation settings of a variable optical attenuator (28th July 2023) - British Standards Institution,
No abstract available